The implantation of Western individualism in the teaching of kinship terms to Nigerian students - Joseph A. Ushie, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
This paper is a contribution to the argument that teaching a language to non-native speakers may translate into cannibalization on the learner‟s culture if the teaching is not made environmentsensitive.The paper also points out how, in an apparently innocuous manner, this process can result in a major shift in the worldview and life ways of the people. The paper derives from the personal experience of my initial exposure to English kinship terms in a second language situation in Nigeria, in which our African cultural peculiarities were not taken into consideration. It thus presents the contrasts between the „Received Meanings‟ of selected kinship terms and their meanings in the Nigerian cultural milieu, and shows the grave wider implications of imposing „Received Meanings‟ on the non-native African learner. It suggests that the teaching of English in the non-native environment be made malleable to the various functional domains of the language, including especially the cultural peculiarities of the learner if the much-cherished global cultural pluralism is to be sustained.